Behavioral study with environmental enrichment for small felines in captivity at the zoological Center of Instruction and War in the Jungle - Silva, Anne; Santos, Sinandra (Pubvet, 2020)
In the Amazon rainforest, several species of wild animals are threatened with extinction, corresponding to the improper exploitation of man in the wild. Thus, the zoo plays an important role in environmental education, preservation and maintenance of species derived from federal organ rescues. This study aims to qualify and quantify the behavioral observations in the pre-enrichment (PRE), enrichment (ENR) and post-enrichment (POS) phases, applying sensory, cognitive and olfactory environmental enrichment items to two Leopardus pardalis females. two female Leopardus wiedii, and one male Puma yagouaroudi captive in Center of Instruction and War in the Jungle. Species showed interest in the enrichment items, indicating increased frequency in the categories locomotion, social interaction and interaction with enrichment in the phase (ENR), but in the phase (POS) these results decreased, resulting in increased frequency in the rest category. Conducting frequent environmental enrichment practices has contributed to the animal welfare of captives.
Keywords: environmental enrichment; ethology; felines; zoo